2009
DOI: 10.1002/app.30162
|View full text |Cite
|
Sign up to set email alerts
|

Poly[4‐(4‐vinylbenzyloxy)‐2‐hydroxylbenzaldehyde] for rapid removal of low concentrations of Pb(II)

Abstract: Poly[4-(4-vinylbenzyloxy)-2-hydroxylbenzaldehyde] was evaluated for removing low concentrations of lead(II) in ppb levels from aqueous media. The effects of the pH condition and the initial lead concentrations on removal were examined. It was found that the metal absorption is best described with the Langmuir model. The R L values obtained between 0.01 and 0.23 indicate that favorable absorption occurs in the studied concentration ranges. The kinetic study revealed that the metal removal proceeds at a very fas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…In our previous study, we found that the surface area of the samples had little impact on the adsorption of heavy‐metal ions on the hybrid materials containing ionic groups. Similar results were also seen in other studies . To further confirm the influence of the pore size and to examine the surface morphology of the previously prepared zwitterionic hybrid materials, the surface FESEM image of samples A–D were observed and are presented in Figure .…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…In our previous study, we found that the surface area of the samples had little impact on the adsorption of heavy‐metal ions on the hybrid materials containing ionic groups. Similar results were also seen in other studies . To further confirm the influence of the pore size and to examine the surface morphology of the previously prepared zwitterionic hybrid materials, the surface FESEM image of samples A–D were observed and are presented in Figure .…”
Section: Resultssupporting
confidence: 80%
“…Similar results were also seen in other studies. 20,21 To further confirm the influence of the pore size and to examine the surface morphology of the previously prepared zwitterionic hybrid materials, the surface FESEM image of samples A-D were observed and are presented in Figure 4.…”
Section: Fesem Imagesmentioning
confidence: 99%